Thinner [videorecording (DVD)] - Burke, Robert (Robert John); Jenney, Lucinda; Licht, Daniel; Oostrum, Kees van, 1953-; Rubinstein, Richard P.; Galin, Mitchell; Holland, Tom, 1943-; Holland, Tom, 1943-; McDowell, Michael, 1950-1999; Mantegna, Joe; Wuhrer, Kari; Constantine, Michael; et al. (Olive Films, 2012)
Based on the best-seller, Stephen King's Thinner stars Robert John Burke and Joe Mantegna in a story of supernatural terror and countdown to the ultimate payback. A 109-year old gypsy, hell-bent on revenge, exacts a curse so shocking it compels its victim to gorge himself in an effort to avoid shrinking away to nothingness. With time running out and a torture so bizarre and powerful, even death seems a more likely option.